2020
DOI: 10.3847/1538-4357/aba757
|View full text |Cite
|
Sign up to set email alerts
|

GRB 140423A: A Case of Stellar Wind to Interstellar Medium Transition in the Afterglow

Abstract: We present very early ground-based optical follow-up observations of gamma-ray burst (GRB) 140423A, which was discovered by the Swift/Burst Alert Telescope (BAT) and by the Fermi/Gamma-Ray Burst Monitor. Its broadband afterglow was monitored by the Swift/X-Ray Telescope and ground-based optical telescopes from T 0 + 70.96 s to 4.8 days after the Swift/BAT trigger. This is one more case of a prompt optical emission observation. The temporal and spectral joint fits of the multiwavelength light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…The posterior probability density functions for the physical parameters, i.e., E k,iso,on , Γ 0 , θ c , θ jet /θ c , θ v /θ c , p, ǫ e , ǫ B , A * , and R tr , are presented in Figure 8, where only the fitting result of GRB 120326A is shown as an example. The optimal result from MCMC fitting is shown in Figure 7 with blue line (XRT) and red line (optical), and the obtained parameters at the 1σ confidence level are reported in Table 1, where the values of the transition radius R tr (i.e., 1.05 × 10 17 cm, 6.31 × 10 16 cm, and 3.98 × 10 17 cm for GRBs 120326A, 120404A and 100814A, respectively) are consistent with those found in other bursts (e.g., Kong et al 2010;Feng & Dai 2011a;Ramirez-Ruiz et al 2001;Li et al 2020). It can be found that both the X-ray afterglow and the optical afterglow of these bumps can be well modelled with an off-axis observed external-forward shock in a free-to-shocked wind environment.…”
Section: Case Studysupporting
confidence: 82%
“…The posterior probability density functions for the physical parameters, i.e., E k,iso,on , Γ 0 , θ c , θ jet /θ c , θ v /θ c , p, ǫ e , ǫ B , A * , and R tr , are presented in Figure 8, where only the fitting result of GRB 120326A is shown as an example. The optimal result from MCMC fitting is shown in Figure 7 with blue line (XRT) and red line (optical), and the obtained parameters at the 1σ confidence level are reported in Table 1, where the values of the transition radius R tr (i.e., 1.05 × 10 17 cm, 6.31 × 10 16 cm, and 3.98 × 10 17 cm for GRBs 120326A, 120404A and 100814A, respectively) are consistent with those found in other bursts (e.g., Kong et al 2010;Feng & Dai 2011a;Ramirez-Ruiz et al 2001;Li et al 2020). It can be found that both the X-ray afterglow and the optical afterglow of these bumps can be well modelled with an off-axis observed external-forward shock in a free-to-shocked wind environment.…”
Section: Case Studysupporting
confidence: 82%
“…There are other possible assumptions that might not necessarily hold true for the afterglow of GRB 160131A: (1) the constant micro-physics parameters, in light of the evidence of the temporal evolution of the micro-physics parameters in the afterglow of GRB 190114C (Misra et al 2021), (2) a unique CBM, as in the case of evidence of the transition from a wind-like to ISMlike CBM in the afterglow of GRB 140423A (Li et al 2020), and (3) a uniform jet model, in light of the evidence of other…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the conventional environments of free stellar wind and the interstellar medium (ISM), abrupt density transitions in the surrounding medium are often mentioned (Dai & Lu 2002). Some studies have explained the sudden rebrightenings, fluctuations, and changes in decay slopes in the afterglow LCs of GRBs using models incorporating density jumps in the medium (e.g., Dai & Wu 2003;Monfardini et al 2006;Li et al 2020a). Numerical simulations have shown the mass outflows from massive stars could create a stellar wind bubble within a certain radius surrounding the star and eventually transition to a uniform ISM (e.g., Eldridge et al 2006).…”
Section: Circumburst Environmentmentioning
confidence: 99%